Sonography as an Adjunct to Digital Mammography in Patients with Dense Breasts - Jha , Anamika; Regmi, Pradeep Raj; Pradhan, Huney; Thakur , Minaxi; Joshi , Birendra Raj (Journal of Nepal Health Research Council, 2025)
Background: Dense breasts are associated with an increased risk of cancer and also mask lesions on mammograms. In our study, we evaluated the role of sonography as an adjunct to digital mammography in patients with dense breasts.Methods: Sonography of 676 female patients with American College of Radiology category C or D mammographic density was done in this prospective cross-sectional analytical study in the Department of Radiology, Tribhuvan University Teaching Hospital. The final imaging diagnosis was classified as per the American College of Radiology Breast Imaging Reporting and Data System categories. Tissue diagnosis was obtained in patients with sonographic category 3 solid lesions larger than 3 cm, category 4 and 5 lesions. The data were tabulated and analyzed using Statistical Package for Social Service (SPSS) for Windows version 22.Results: Additional sonography confirmed all BIRADS 1 mammograms as normal or benign, 95.7 % (112) of inconclusive, and 82.8% (n=135) of BIRADS 3 ones as benign. It had higher sensitivity and negative predictive value (100%) than mammography with similar accuracy. Most patients (479, 70.9%) had diagnostic indications. There were 540 (79.9%) cases in ACR BIRADS category c. A final diagnosis of benign (316, 46.7%) was most common, followed by normal (293, 43.4%) and malignant (67, 9.9%). The majority of the malignant lesions were Invasive Ductal Carcinoma (59, 88%). Conclusions: Additional sonography confirmed mammography findings as normal, benign, or suspicious for malignancy, definitely described morphology and extent of mass, and also guided biopsy. It had higher sensitivity than mammography in dense breasts. Keywords: Breast density; mammography; ultrasonography mammary.